Colonialism as a Profession: A Precursor of Moral Degradation in Joseph Conrad’s Heart of Darkness (Journal of Social Sciences Review, 2023)
This paper examines the negative effects of colonialism as a profession on the European colonizers, particularly Mr Kurtz in the novella Heart of Darkness. The present study intends to analyze the idea that not only the African wilderness is responsible for the moral corruption of Mr Kurtz and his companions, but his profession is also a reasonable cause. The paper also explores how the narrator of the story, Marlow, who is also a part of the colonial system, distorts reality and blames only the African environment for the mental degradation of Mr Kurtz. In this regard, Frantz Fanon’s concept of violence is used to illustrate these problems in the given novella. The study concludes that although Marlow only reprehends the African wilderness for the moral collapse of Mr Kurtz, colonialism as a violent profession is also a substantial factor responsible for his extreme behaviour.
Keywords: Heart of Darkness; Joseph Conrad; Moral Degradation; Colonization; Frantz Fanon; Insanity; Violence